A Framework for Conditional Sunset Clauses - Gangur, Petr (Review of European and Comparative Law, 2025)
Sunset clauses are a legislative method ensuring that a law expires at a certain time. This legislative tool can be further divided into conditional and unconditional sunset clauses. While unconditional sunset clauses are well-known and without much controversy – the duration of a law in such a case is usually dependent on a specific date – conditional sunset clauses are more complex and less debated. This article develops a structured framework of conditional sunset clauses that distinguishes these clauses primarily by a measure of legal certainty. The article divides conditional sunset clauses into three distinct categories: formal, semi-formal, and non-formal sunset clauses. With examples of their use across jurisdictions, it shows their differences – formal sunset clauses are based on public authority and are an official source of law (they are typically also published in an official statute book or public register), while semi-formal ones are also based on public authority, but any transparently published information is sufficient for their classification. Non-formal sunset clauses may be linked to actors other than the public authority and the reference to them may be non-public; however, the key question regarding these sunset clauses is whether they can be considered legal. This study highlights the challenges in applying conditional sunset clauses, their impact on the predictability of law, the separation of powers and the democratic rule of law as a whole. This framework enables legislators, judges and especially legal scholars to effectively classify these sunset clauses and to contrast them with their local legal orders, constitutions and laws.